The guardians of the living dead: traumatic experiences of hangmen in South Africa - Mashabela, Pelmos (Acta criminologica, 2019)
Literature is awash with the secrecy surrounding prison, prison administration and prison records particularly during the dark years of apartheid. Invariably, corrections and penitentiaries all over the world are notorious for their secrecy and not overly open for public scrutiny. While this is the case, there is a need for a comprehensive approach to address the emerging psychosocial problems encountered by correctional officials. Even more so for correctional personnel who, during apartheid years, were responsible for the execution of inmates sentenced to death. Thus, although the history of capital punishment was studied in South Africa prior to the abolishment of capital punishment in 1995, there are no scientific studies done on its impact on correctional officials. There further is very little evidence to suggest that correctional personnel and, in particular, warders, who were involved in the executions, received any form of intervention from the State or the Department concerned. The central argument of this article is that there is a need for such interventions in the democratic dispensation as these correctional officers still exhibit signs of emotional and psychological trauma. While no interviews were conducted with death row correctional personnel, the anecdotes from archival data are relied upon to inform intervention strategies for these warders. Organisationally, the article is structured into four epochs. First an account of the extent of executions in apartheid South Africa is given. This is followed by a brief overview of the methods of executions. A third layer of the article focuses on the identities of the hangman or death row warders. The impact of executions of these correctional personnel is addressed in the fourth section. In the last section, a central argument is made for intervention programming for death row correctional warders who remain in the service within corrections.